DEVELOPMENT OF THE RELATIONSHIP OF THEORY AND PRACTICE IN THE PROFESSIONAL ACTIVITY OF SOCIAL WORKER - Dirgėlienė, Indrė (Acta Paedagogica Vilnensia, 2008)
The activity of the social worker is multiple and complex, and the result is difficult to predict. The tension between the personal and professional identity arises, and personal, professional, and social experience interact to lay the foundation for the competence of the social worker to intervene in the case of a crisis.The process of social work and the system of competence of the social worker embrace a reflective model that stimulates to continuously revise one’s own professional experience.On the basis of empiric data (accumulated during a research project Design of a Supervision Application Model in the Development of Professional Competences of Social Workers, subsidized by the National Fund of Science and Studies and carried out by I. Dirgėlienė, A. Kiaunytė, V. Kanišauskaitė, J. Ruškus and N. Večkienė, 2007), the article seeks to reveal the experience of the development of the interrelationship between theory and practice in the professional activity of the social worker. As witnessed by the data of the research, the application of theoretical knowledge to practice was recognized by respondents – university graduates, senior executives (the fact also linked with higher education). The respondents who recognized the link of theory and practice expressed the need for the knowledge of general professional subjects, as well as for the knowledge in the fields of the humanities, social, and economic sciences. One can believe that the attitude was influenced by studies based on the model of reflective thinking, when in the process of studying students were enabled to assess the significance of the integration of knowledge, values, and skills in the context of social work. Those who recognized the significance of the link between theory and practice were characterized by self-confidence that facilitated the overcoming of the stages of the social work process; those respondents were able to use the resources of specialist help. That was the attribute of independent learning. Those were respondents ready to implement the idea of life-long learning.Key words: professional experience, personal and professional identity, reflection, interaction, learning society, a professional ‘overburning syndrome’.
Keywords: professional experience; reflection; interaction; learning society; experiential learning